2012
DOI: 10.1007/s10162-012-0324-5
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Gene Expression in the Mouse Inner Ear Using Cre-loxP

Abstract: In recent years, there has been significant progress in the use of Cre-loxP technology for conditional gene expression in the inner ear. Here, we introduce the basic concepts of this powerful technology, emphasizing the differences between Cre and CreER. We describe the creation and Cre expression pattern of each Cre and CreER mouse line that has been reported to have expression in auditory and vestibular organs. We compare the Cre expression patterns between Atoh1-CreER TM and Atoh1-CreER T2 and report a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 168 publications
8
80
0
Order By: Relevance
“…4G-H’’’). Finally, consistent with the observation that iCre activity in Fgfr3 iCreER+ mice was present in limited number of endogenous OHCs (Cox et al, 2012), a few EGFP+/calbindin+ cells (endogenous HCs with iCre activity) were found in the experimental group. However, the number of EGFP+/calbindin+ cells was similar between the experimental and control groups, suggesting that Sox2-negative OPCs and DCs also did not change fate to become HCs.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…4G-H’’’). Finally, consistent with the observation that iCre activity in Fgfr3 iCreER+ mice was present in limited number of endogenous OHCs (Cox et al, 2012), a few EGFP+/calbindin+ cells (endogenous HCs with iCre activity) were found in the experimental group. However, the number of EGFP+/calbindin+ cells was similar between the experimental and control groups, suggesting that Sox2-negative OPCs and DCs also did not change fate to become HCs.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, we instead characterized the Fgfr3 iCreER+ transgenic mouse (Young et al, 2010). When tamoxifen was given at P0 and P1, inside the organ of Corti, the iCre activity of Fgfr3 iCreER+ is primarily restricted into IPCs, OPCs and DCs (Cox et al, 2012). Of note, iCre+ OHCs, Hensen’s cells or Claudius cells were also observed, but iCre+ IHCs and inner phalangeal cells (IPHs) were never observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study underscore the potential confounding effects from haploinsufficiency when using knockin mouse models (79). For example, the Foxg1-Cre mouse line can have brain deficits that probably stem from alterations in proliferation, possibly as a result of haploinsufficiency (80)(81)(82).…”
Section: Sox2mentioning
confidence: 73%
“…For example, the traditional bacteriophage-derived Cre is not optimal for eukaryotes due to its codon usage of prokaryotes, and its 65 CpG dinucleotides may induce epigenetic silencing (38). To overcome these potential problems, we generated vGLUT1-iCreERT2, vGLUT2-iCreERT2, and GAD65-iCreERT2 mutant mice with a knockin of iCreERT2 (38,39) into the Vglut1, Vglut2, or GAD65 locus. Mice received 8 daily injection of tamoxifen 1 week before use (40).…”
Section: Methodsmentioning
confidence: 99%